THE EFFECT OF LEARNING MODEL PICTURE AND PICTURE AND READING INTEREST TOWARD STUDENTS’ POETRY WRITING SKILLS OF 5TH GRADE PRIMARY SCHOOL STUDENTS - Resti Audina; St. Y. Slamet; Jenny Indrastoeti Siti Poerwanti (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
The study aims to know the effect of Picture and Picture learning model and reading intertest toward poetry writing skills. The study  used quasi experimental type of quantitative approach with Anova two-way analysis of variance. The samples were taken by using cluster random sampling. The data were collected by doing test. The instrument was tested using factor analysis. The data were analyzed using descriptive analysis and statistical parametric consisted of prerequisite test (normality and homogeneity test), hypothesis test (Anova two-way analysis). Based on the results of t-test analysis at significance level a = 0.05, obtained FAB = 4,14 > F0,05;1,57 = 4,01. Thus, it can be concluded that there is an effect of Picture and Picture learning model and reading intertest toward poetry writing skills.